Analisis Keandalan Pada Komponen Mesin Pencetak Koran Webb Offset - Purwatiningsih, Dyah Retno; F, Haris (Department Industrial Engineering, University of Muhammadiyah Malang, 2002)
PT. Temprina Media Grafika is one of Jawa Pos Group Company that print newspaper and magazine. To decline when they have to buy machine component of newspaper printer which very needed can be found with measuring component reliability to keep maintaining. Based on Kolmogorov - Smirnov test can be found each component's distribution to find variables which used to count reliability function.